UTILIZING LOCAL ENVIRONMENT EXPLORATION METHOD FOR JUNIOR HIGH SCHOOL IN ELT - Reza Ainun Najib, Muhammad; Giri Aditama, Madya; Huda Shofyana, Maila; Putri, Rosalidya (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2025)
This study explored the implementation of the Local Environment Exploration Method in English Language Teaching (ELT) at SMP Negeri 1 Weleri, examining its impact on student engagement, contextual relevance, cultural awareness, and teacher adaptation. Using a qualitative phenomenological approach, data were collected through interviews, classroom observations, and document analysis with teachers and students. The findings reveal that integrating local environmental contexts into ELT enhances language learning by making lessons more meaningful and relatable, increasing students' motivation and active participation. Moreover, the method promotes environmental stewardship and cultural identity by connecting language acquisition with local traditions and natural surroundings. Teachers reported improved pedagogical skills through innovative lesson planning and experiential learning activities, although challenges related to resource limitations and scheduling were identified. This study highlights the dual benefit of this method, which fosters linguistic competence while enriching cultural awareness, thus offering a holistic approach to ELT. The findings contribute to the growing body of literature on contextualized learning and provide practical insights for educators seeking to integrate culturally relevant and place-based teaching methods. Future research should investigate the long-term effects of this method on language proficiency and cultural preservation in diverse educational contexts.